Effects of Age and Body Size on Ovarian Development and Fecundity in Culex quinquefasciatus (Diptera: Culicidae) - Latif, Afsana Al; Bashar, Kabirul; Akhi, Tonima Akther; Mim, Tabassum Mostofa; Haque, Md Mujammel; Chaiti, Nusrat Jahan; Jahan, Neshat; Apon, Farhan Chowdhury (Bangladesh Journal of Zoology, 2025)
Abstract not available Bangladesh J. Zool. 53(2): 231-235, 2025